2013
DOI: 10.3390/molecules181012916
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Lung Cancer Activities of Steroidal Saponins of P. polyphylla Smith var. chinensis (Franch.) Hara through Enhanced Immunostimulation in Experimental Lewis Tumor-Bearing C57BL/6 Mice and Induction of Apoptosis in the A549 Cell Line

Abstract: P. polyphylla Smith var. chinensis (Franch.) Hara (PPSCFH) has been used as medicinal Paris for the prevention and treatment of cancers in China for thousands of years. Its main components, steroidal saponins (PRS), have been confirmed to inhibit tumor OPEN ACCESSMolecules 2013, 18 12917 growth. In the present study, the immunostimulation of PRS was investigated in Lewis bearing-C57BL/6 mice while the induction of apoptosis in A549 cells was also studied. The treatment with PRS (2.5, 5.0 and 7.5 mg/kg) signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…PSI, which has a molecular formula of C 44 H 70 O 16 (Fig. 1), was purchased at a purity of >99% from the Zhejiang Institute for Food and Drug Control (batch no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PSI, which has a molecular formula of C 44 H 70 O 16 (Fig. 1), was purchased at a purity of >99% from the Zhejiang Institute for Food and Drug Control (batch no.…”
Section: Methodsmentioning
confidence: 99%
“…Hand-Mazz. Rhizoma paridis has been reported to exert numerous pharmacological effects, including anti-inflammatory, hemostatic and anti-cancer effects, and was shown to exhibit inhibitory effects on tumor growth in numerous studies using hepatic, gastric or nasopharyngeal carcinoma models (11)(12)(13)(14)(15)(16). Furthermore, Paris saponin II significantly inhibited tumor growth by 70% in the human SKOV3 ovarian cancer xenograft model (17), and Paris saponin H showed a marked cytotoxic activity on A549 cells with an IC 50 value of 1.53±0.08 µg/ml (18).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, RPS treatment did not only make tumor masses grow much slower than the model ones, but also inhibit the pulmonary metastasis in Lewis mice (Figures and ). According to the previous reports, the inhibition of RPS on pulmonary metastases might be associated with the amelioration of inflammation responses, decrease in ROS, upregulation of TIMP‐2 and downregulation of MMP‐2 and MMP‐9 levels . However, these researches did not reveal the antitumor mechanism of RPS from a holistic view.…”
Section: Discussionmentioning
confidence: 91%
“…Rhizoma paridis saponins (RPS) as the effective parts of Paris polyphylla showed strong anti‐lung cancer and pulmonary metastasis in different models . According to the previous reports, the inhibition of RPS on pulmonary metastasis might be associated with the amelioration of inflammation responses, decrease in reactive oxygen species (ROS), upregulation of TIMP‐2 and downregulation of MMP‐2 and MMP‐9 levels . Meanwhile, other researchers reported that some monomers isolated from RPS exhibited improving the body's immune system by diosgenyl saponins and inhibition of angiogenesis by Paris saponin II …”
Section: Introductionmentioning
confidence: 99%
“…Figure 4C indicates that the plasma TNF-α of 25.5 µmol/kg Dex treated inflammatory mice is significantly lower than those of NS treated inflammatory mice and Sham mice, but is significantly higher than those of 25.5 µmol/kg RGDS-Dex, RGDV-Dex and RGDF-Dex treated inflammatory mice. A549 cells were widely used to respond the cross talk of inflammation and DNA replication, [30][31][32] and some anti-inflammatory agents were reported to be able to counteract both pro-inflammatory effect and DNA replication. Thus it is hypothesized that via dcreasing plasma TNF-α and IL-8 RGD-tetrapeptide covalent modification enhances the anti-inflammatory activity.…”
Section: Rgd-tetrapeptide Covalent Modification Enhances the Antiinflmentioning
confidence: 99%